PENINGKATAN HASIL BELAJAR TENIS MEJA MELALUI PENDEKATAN PERMAINAN BOUNCING BALL SISWA SMP (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
Table tennis is a game which is difficult for junior high school students . The problem in this research is thereany increasing in learning through a bouncing ball l on 7th of SMP N 1 Kragan?. This research aims toimprove learning through a bouncing ball approach for junior high school students in the learning of PhysicalEducation, Sport and Health. This research uses classroom action research. In the implementation of the firstcycle and second cycle of meetings held 1 meeting. The subjects were class VII SMP Negeri 1 Kragan, Kragan,Rembang. The Instruments in data collection obtained from observations at learning, performance test andwritten test. The results of the percentage of completion on the first cycle can achieve KKM on 47% of the totalnumber of students and in the second cycle increased to 87.5%. Based on the above results, it can be concludedthat the implementation of a table tennis ball with bouncing ball game approach can improve learningoutcomes in 7th grades student of SMP Negeri 1 Kragan. Physical Education teachers are expected to usebouncing ball in teaching.